Kewenangan BPSK dan BMAI dalam menyelesaikan sengketa asuransi Antara perusahaan asuransi dan pemegang polis asuransi - Sipahutar, Anjani; Sipahutar, Ervina Sari; Fauzi, Muhammad (Jurnal Normatif, 2024)
Disputes can occur in various sectors, one of which occurs in the insurance sector. If there is a dispute or insurance dispute between the insurer and the insured, the parties to the dispute can choose to resolve the dispute they are experiencing through court/litigation or outside court/non-litigation. Dispute resolution that is resolved through court/litigation is regulated in Article 1266 of the Civil Code, and dispute resolution outside of court can be done through Alternative Dispute Resolution (ADR). Based on statutory regulations in effect until 2019, the LAPS established for disputes in the insurance sector is the Indonesian Insurance Mediation and Arbitration Agency (BMAI). One example of a dispute in the insurance sector that was resolved through alternative dispute resolution is the case of Decision Number 17/Pdt.Sus-BPSK/2021/PN Llg